The influence foreign countries in creation of the mathematics syllabus in Lithuania between two world wars - Ragelytė, Birutė; Paukštienė, Alma (Lietuvos matematikos rinkinys, 2023)
The influence foreign countries in creation of the mathematic syllabus in Lithuania between two world wars is presented in this article. Ideas of Klein and Merane program are discussed in this article. The influence and experience of foreign countries in creating the mathematics syllab us are introduced. Results of analysis Lithuanian mathematics syllabus and foreign counties (France, Austria, Germany, Italy) of this period are presented in this article.
Keywords: mathematics syllabus; ideas of Klein; Merane program; analysis foreign countries and Lithuanian mathematics syllabus in begin XX a.